Differences of Students' Mathematics Learning Results using Student Team Achievement Division (STAD) and Expository Methods On Materials Build A Flat of A Rquange - Yenni Arnas; M. Sutarjo; Otto Fajarianto (EduLine: Journal of Education and Learning Innovation, 2022)
In education in Indonesia, teacher upgrading is carried out, especially discussing the learning system that is suitable for use in the classroom. Among the existing learning systems is the Cooperative Learning system. Cooperative Learning learning system is defined as a group learning activity organized by the principle that learning should be based on changes in social information among its members, and take responsibility for their own learning and be encouraged to improve the learning of other members. This research is to see the Differences in Students' Mathematics Learning Outcomes Using the Student Team Achievement Division (STAD) Method and the Expository Method. The research method uses experiments. Based on calculations and data analysis, this study has shown that there are differences in learning outcomes between the treated class (experimental) and the untreated class (control). This proves that the mathematics learning outcomes of students whose learning process uses the Student Team Achievement Division (STAD) method are better than the mathematics learning outcomes of students whose learning process uses the expository method.